Dana Keistimewaan Daerah Istimewa Yogyakarta Dan Kontribusinya Untuk Masyarakat - Christian Budimantoro; Supriyanto (Institut Riset dan Pengembangan Indonesia, 2024)
Indonesia, as a country whose economy still depends on public sector financing, hopes that decentralization policies can significantly improve the welfare of its people. However, in reality, this expectation has not been widely met. This is seen in the Special Region of Yogyakarta (DIY), which has special authority in managing its administrative affairs. The Indonesian government enacted Constitution 13 of 2012 on the Special Privileges of DIY includes five areas: the Procedure for Filling Positions, Status, Duties, and Authority of the Governor and Vice Governor; Institutional Affairs; Cultural Affairs; Land Affairs; and Spatial Planning. . With the enactment of this law, it is expected that the DIY government can use it as a guideline or foundation in efforts to ensure the well-being of its citizens. However, this expectation has not yet been fully realized. This research aims to identify and explain the Special Autonomy Fund of DIY and its contribution to efforts to improve the welfare of the community. The type of research used is a qualitative approach. The method used for data collection employs observation techniques and document analysis.